2017
DOI: 10.1111/nph.14780
|View full text |Cite
|
Sign up to set email alerts
|

TGACGBINDING FACTOR 1 (TGA1) and TGA4 regulate salicylic acid and pipecolic acid biosynthesis by modulating the expression of SYSTEMIC ACQUIRED RESISTANCE DEFICIENT 1 (SARD1) and CALMODULINBINDING PROTEIN 60g (CBP60g)

Abstract: Summary Salicylic acid (SA) and pipecolic acid (Pip) play important roles in plant immunity. Here we analyzed the roles of transcription factors TGACG‐BINDING FACTOR 1 (TGA1) and TGA4 in regulating SA and Pip biosynthesis in Arabidopsis thaliana. We quantified the expression levels of SYSTEMIC ACQUIRED RESISTANCE DEFICIENT 1 (SARD1) and CALMODULIN‐BINDING PROTEIN 60g (CBP60g), which encode two master transcription factors of plant immunity, and the accumulation of SA and Pip in tga1‐1 tga4‐1 mutant plants. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 27 publications
3
171
0
Order By: Relevance
“…These data indicate that SA biosynthesis is a dynamic and tempo‐spatially controlled process in plants. Recently, it was reported that two Arabidopsis bZIP transcription factors (TGA1 and TGA4) are involved in the regulation of SA biosynthesis (Sun et al ., ). In our study, we observed that expression changes in StbZIP61 were correlated with changes in StICS1 .…”
Section: Discussionmentioning
confidence: 97%
“…These data indicate that SA biosynthesis is a dynamic and tempo‐spatially controlled process in plants. Recently, it was reported that two Arabidopsis bZIP transcription factors (TGA1 and TGA4) are involved in the regulation of SA biosynthesis (Sun et al ., ). In our study, we observed that expression changes in StbZIP61 were correlated with changes in StICS1 .…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, SARD1 , which was slightly but significantly activated by TGA1/TGA4 in the absence of SA (Fig. 1) and after Psm infections (Sun et al ., 2018), contains a TGACGTCA motif at position - 212 bps. The G-box is significantly depleted in promoters being less activated in sid2 tga1 tga4 plants.…”
Section: Resultsmentioning
confidence: 82%
“…In order to address the question whether the disulfide bridge-forming cysteines of TGA1 that become reduced in SA-treated plants indeed play a role for accurate transcription of SA-responsive genes, we first tested SA-induced expression of SARD1 , which has been recently identified as a target gene of TGA1/TGA4 (Sun et al, 2018). However, in contrast to Psm infections, spraying with 1 mM SA resulted in TGA1/TGA4-independent SARD1 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations